(untitled) (Annals of Medical Research, 2023)
Aim: Human leukocyte antigen-B27 (HLA-B27) binds antigenic peptides in the structure of some viruses and presents them to cytotoxic T lymphocytes and plays a role in the immune response against these viruses. It has also been found to be associated with auto-immunity as an inverse relationship and is associated with a number of auto-immune inflammatory diseases, especially Ankylosing Spondylitis (AS). Our aim in this study is to determine the role of HLA-B27 in Severe Acute Respiratory Syndrome (SARS)-Cov-2 (Coronavirus Disease-COVID-19). Materials and Methods: 90 HLA-B27 positive and 96 HLA-B27 negative cases were included in the study. COVID-19 Polymerase Chain Reaction (PCR) results and Thorax Computed Tomography (CT) results, hospitalization and death records of the cases were retrospectively analyzed from the system records. Results were compared between HLA-B27 positive and negative groups. Results: Of the HLA-B27 positive cases, 32.2% had COVID-19 positivity, 5.6% had COVID-19 lung involvement. 44.8% of HLA-B27 negative cases had COVID-19 positivity and 11.5% had lung involvement. There was no significant difference between the HLA-B27 positive and negative groups in terms of having COVID-19 infection, lung involvement, hospitalization and death rates. Conclusion: The results of our study show that HLA-B27 does not have a protective role in terms of having COVID-19 and lung involvement. Again, since no auto-immunity-related SARS was observed in any of the patients, it can be said that it did not increase the severity of the hyper-immunity-related disease and did not increase the risk of death in particular for COVID-19. These results need to be supported by more studies.